2023
DOI: 10.1002/oby.23677
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 agonists combined with sodium‐glucose cotransporter‐2 inhibitors reduce weight in type 1 diabetes

Abstract: ObjectiveThis study evaluated whether adding sodium‐glucose cotransporter‐2 inhibitors (SGLT2i) and/or glucagon‐like peptide‐1 receptor agonists (GLP1‐RA) to insulin reduced weight and glycemia in people with type 1 diabetes.MethodsThis retrospective analysis of electronic health records evaluated 296 people with type 1 diabetes over 12 months after medications were first prescribed. Four groups were defined: control n = 80, SGLT2i n = 94, GLP1‐RA n = 82, and combination of drugs (Combo) n = 40. We measured ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Pharmacotherapies including glucagon-like peptide 1 agonists, SGLT2i, and other antidiabetic medications indirectly promote weight loss while also providing metabolic benefits. 38) …”
Section: Comorbidities In Hfmref and Hfpefmentioning
confidence: 99%
“…Pharmacotherapies including glucagon-like peptide 1 agonists, SGLT2i, and other antidiabetic medications indirectly promote weight loss while also providing metabolic benefits. 38) …”
Section: Comorbidities In Hfmref and Hfpefmentioning
confidence: 99%
“…More recently, a 52-week study ( n = 76) yielded comparable results for daily insulin dose and HbA1c but indicated a more substantial reduction in body weight (−5.1 kg) [ 76 ]. In another study, combining both GLP1-RA and SGLT2 inhibitor resulted in the greatest percentage of weight loss (9.0%) compared to a single prescription, after 12 months [ 77 ]. This combination improved HbA1c, total cholesterol, and LDL-cholesterol while remaining safe from DKA and hypoglycaemia [ 77 ].…”
Section: Treatments For Obesity In Patients With Type 1 Diabetesmentioning
confidence: 99%
“…In another study, combining both GLP1-RA and SGLT2 inhibitor resulted in the greatest percentage of weight loss (9.0%) compared to a single prescription, after 12 months [ 77 ]. This combination improved HbA1c, total cholesterol, and LDL-cholesterol while remaining safe from DKA and hypoglycaemia [ 77 ]. Notably, the implementation of a structured risk prevention programme and sick-day guidance were applied to all enroled patients, [ 77 ] highlighting the importance of investing in patient education and the provision of adaptable care.…”
Section: Treatments For Obesity In Patients With Type 1 Diabetesmentioning
confidence: 99%
“…30 This combination pharmacotherapy achieves more significant reductions in bodyweight and fat mass compared with monotherapy. 32,33 The efficacy and safety of GLP-1 agonists alone or in combination with SGLT2i have not been investigated in horses.…”
mentioning
confidence: 99%
“…Co‐administration of SGLT2i with drugs that reduce food intake (e.g., glucagon‐like peptide 1 [GLP‐1] agonists) is now commonplace in human medicine to mitigate the mechanisms that counteract weight loss with long‐term use of SGLT2i 30 . This combination pharmacotherapy achieves more significant reductions in bodyweight and fat mass compared with monotherapy 32,33 . The efficacy and safety of GLP‐1 agonists alone or in combination with SGLT2i have not been investigated in horses.…”
mentioning
confidence: 99%